2017
DOI: 10.3201/eid2310.170468
|View full text |Cite
|
Sign up to set email alerts
|

Six-Month Response to Delamanid Treatment in MDR TB Patients

Abstract: Delamanid, recently available for the treatment of multidrug-resistant tuberculosis (MDR TB), has had limited use outside clinical trials. We present the early treatment results for 53 patients from 7 countries who received a delamanid-containing treatment for MDR TB. Results show good tolerability and treatment response at 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 5 publications
2
23
0
3
Order By: Relevance
“…Over the past 2 years, a series of reports showed that treatment outcomes in patients with drug-resistant TB could be improved using new combinations of drugs given for shorter periods of time, better selecting the "old" drugs to include in the treatment regimen or introducing new drugs for prolonged periods of time [15,[22][23][24][25][26][27].…”
Section: Dots-plusmentioning
confidence: 99%
“…Over the past 2 years, a series of reports showed that treatment outcomes in patients with drug-resistant TB could be improved using new combinations of drugs given for shorter periods of time, better selecting the "old" drugs to include in the treatment regimen or introducing new drugs for prolonged periods of time [15,[22][23][24][25][26][27].…”
Section: Dots-plusmentioning
confidence: 99%
“…Not only clinical trials but also clinical experiences have shown that bedaquiline and delamanid are promising new anti-TB drugs, with good efficacy and safety in the treatment of MDR-TB [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. However, further data regarding their efficacy and safety, including the effects on QT prolongation, in patients with quinolone-resistant MDR-TB and XDR-TB are still required [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…(2) Case reports have demonstrated the safety of delamanid in the treatment of complicated MDR‐TB, including one showing prolonged use for 24 months in a child with XDR‐TB…”
Section: Mdr‐tb: Repurposed and Novel Drugsmentioning
confidence: 99%
“…A regimen containing linezolid, bedaquiline and delamanid may be adequate for the most difficult-totreat MDR-TB, but sequential acquisition of drug resistance to bedaquiline and delamanid, 19 and to linezolid and delamanid, 112 has been reported. This may be anticipated, as delamanid is prone to bacillary drug resistance, 117,118 and the 120-week culture conversion rates in patients with pre-XDR-and XDR-TB given an 108 Its open-label extension suggested that delamanid used for more than 6 months, in comparison with its use for less than 2 months, significantly increased favourable outcomes (cure or treatment completion) from 55% to 74.5%, and significantly reduced mortality from 8.3% to 1.0% 109 (4) Otsuka Trial 213, involving use of delamanid at 100 mg bd for the first 2 months and 200 mg once daily for the next 4 months, showed small benefit from adding delamanid to an optimized background regimen, although delamanid may help prevent amplification of drug resistance 110 (1) Although delamanid is associated with QT prolongation, the effect predictably maximizes within 8 weeks of treatment, without associated cardiac clinical manifestations, and is not materially affected by concomitant use of levofloxacin and clofazimine 111 (2) Case reports have demonstrated the safety of delamanid in the treatment of complicated MDR-TB, [112][113][114][115] including one showing prolonged use for 24 months in a child with XDR-TB 116 (3) Trial 213 found no significant difference regarding treatment-emergent adverse events, drug-drug interactions between delamanid and antiretroviral drugs, and prolongation of the corrected QT interval 110 (4) With a relatively high propensity to develop bacillary drug resistance, 117,118 delamanid may be better used with potent companion agents that are less prone to develop bacillary drug resistance, for example, linezolid or bedaquiline 8,112 Pretomanid (PA-824) (1) Being a nitroimidazole that shares the same mechanism of action with delamanid, pretomanid is bactericidal against actively replicating mycobacteria (inhibiting mycolic acid biosynthesis) and non-replicating mycobacteria (generating nitric oxide inside the tubercle bacilli) 117,119,120 (1) Owing to similar structure, pretomanid expectedly shares cross-resistance with delamanid as well as a relatively high propensity to acquiring bacillary drug resistance (2) Not yet approved for use in clinical practice optimized background regimen plus bedaquiline in a clinical trial setting were only 70.5% and 62.2%, respectively. 121 At least three case studies have reported combined use of bedaquiline with delamanid among patients with XDR-TB, [122]…”
Section: Clofaziminementioning
confidence: 99%